Sustentabilidade de agroecossistemas familiares em regiões semiáridas da Itália e do Brasil - Sousa, Breno Henrique de (2021)
Family farming has an important contribution to food security and to achieving the Sustainable Development Goals [SDG] in the world. Its modes of production contribute to the reduction of rural poverty, representing an alternative and counter-hegemonic way of sustainable rural development. Family farms located in semi-arid areas of the world are particularly challenged by adverse ecological and climatic conditions, in addition to the systemic development problems often present in these regions. This thesis was developed between 2017 and 2021, at a bi-national level, in Italy and Brazil, and has the main goals of diagnosing and comparatively analyzing the sustainability strategies of family agroecosystems in semiarid regions of these two countries. In addition to the dynamics of coexistence with the semi-arid region, it was possible to identify the sector's adaptive strategies in view of the homogenizing pressures of the liberal market logic, verifying whether there is a tendency to homogenize these strategies or, instead, if we can find diversified responses. A multi-level analysis strategy was adopted using mixed methods and structured in four articles. In each country, local and regional analyzes were carried out, which were integrated by the comparative method in regional studies in the last chapter of this thesis. The regional stages were carried out in Sicily, Southern Italy, and in the semi-arid region of Paraiba, in the Northeast of Brazil, where the historiography, development panorama and context of family farming were analyzed, using the mixed method of the Concurrent Transformative Strategy type, with qualitative predominance, the theoretical perspective of Sustainable Rural Development [DRS]. The local stages were conducted in the municipality of Calatafimi Segesta, province of Trapani, region of Sicily; and in the municipality of Solânea, in the semiarid region of the state of Paraíba, where the sustainability measurement of family agroecosystems was carried out using the Framework for Evaluation of Natural Resource Management Systems incorporating Sustainability Indicators [MESMIS]. In total, 78 family agroecosystems were analyzed, 32 in Sicily and 46 in Paraíba. The results reveal that both realities underwent a process of formation of the troubled agrarian space, marked by civilizational and social ruptures that contributed to the disruption of social capital and low socioeconomic development. However, several factors such as agrarian reform contributed to the establishment of a general panorama of mini-farm ownership in Sicily, while in Paraíba, despite this problem affecting family farming, latifundia predominate in the hands of a small elite. In Sicily, sustainability strategies mainly follow a conventional path that includes land concentration, technological and productive chain re-qualification and market strategies such as the valorization of native varieties. Alternatively, and on a smaller scale, multifunctionality is adopted, which includes rural tourism, clean energy production, organic and diversified production and direct sales to consumers. In Paraíba, the adoption of agroecological dynamics, including social and productive reorganization within a community logic, is until now the only viable option for the sector. Despite facing similar difficulties and the homogenizing pressure of the market, it was found that family farming in these places found different viable options that have allowed their survival and the preservation of their modes of production.